A Thieno[3, 2‐c]Isoquinolin‐5(4H)‐One Building Block for Efficient Thick‐Film Solar Cells. Issue 20 (19th April 2018) - Li, Dan; Xiao, Zuo; Wang, Shizhe; Geng, Xinjian; Yang, Shangfeng; Fang, Junfeng; Yang, Huai; Ding, Liming
Abstract: An aromatic lactam acceptor unit, thieno[3, 2‐c]isoquinolin‐5(4H)‐one (TIQ), is developed. Compared with its analogues, dithieno[3, 2‐b:2′, 3′‐d]pyridin‐5(4H)‐one (DTP) and phenanthridin‐6(5H)‐one (PN), TIQ shows its advantage in constructing donor–acceptor (D–A) copolymers for efficient solar cells. TIQ‐based D–A copolymer PTIQ4TFBT delivers a power conversion efficiency (PCE) of 10.16% in polymer:fullerene solar cells, while those based on DTP and PN copolymers, PDTP4TFBT and PPN4TFBT, afford PCEs around 8.5%. The higher performance of PTIQ4TFBT:PC71 BM solar cells originates from enhanced short‐circuit current density ( J sc ) and fill factor (FF), because of favorable morphology, less bimolecular recombination, and balanced charge transport in the active layer. Moreover, the performance for PTIQ4TFBT:PC71 BM solar cells is less sensitive to active layer thickness than PDTP4TFBT:PC71 BM and PPN4TFBT:PC71 BM solar cells. Over 8% PCEs can be obtained from PTIQ4TFBT:PC71 BM solar cells when the active layer thickness is over 500 nm. Abstract : A thieno[3, 2‐c]isoquinolin‐5(4H)‐one building block is designed. PTIQ4TFBT:PC71 BM solar cells present less bimolecular recombination and balanced charge transport, giving a power conversion efficiency (PCE) of 10.16% with an active layer thickness of 267 nm. Over 8% PCEs can be obtained with active layer thicknesses over 500 nm.